Comparison of marine sampling methods for organic contaminants: Passive samplers, water extractions, and live oyster deployment. (August 2015) - Raub, Kristin B.; Vlahos, Penny; Whitney, Michael
Abstract: Laboratory and field trials evaluated the efficacy of three methods of detecting aquatic pesticide concentrations. Currently used pesticides: atrazine, metolachlor, and diazinon and legacy pesticide dieldrin were targeted. Pesticides were extracted using solid-phase extraction (SPE) of water samples, titanium plate passive samplers coated in ethylene vinyl acetate (EVA) and eastern oysters ( Crassostrea viginica ) as biosamplers. A laboratory study assessed the extraction efficiencies and precision of each method. Passive samplers yielded the highest precision of the three methods (RSD: 3–14% EVA plates; 19–60% oysters; and 25–56% water samples). Equilibrium partition coefficients were derived. A significant relationship was found between the concentration in oyster tissue and the ambient aquatic concentration. In the field (Housatonic River, CT (U.S.)) water sampling (n = 5) detected atrazine at 1.61–7.31 μg L −1, oyster sampling (n = 2 × 15) detected dieldrin at n.d.–0.096 μg L −1  SW and the passive samplers (n = 5 × 3) detected atrazine at 0.97–3.78 μg L −1  SW and dieldrin at n.d.–0.68 μg L −1  SW. Highlights: EVA plates had highest precision of the three methods in lab and field trials. EVA plates had the highest extraction efficiency of the three methods. Of the methods, EVA plates detect compounds with broadest range of properties. EVA plate performance is an effective passive sampling method. Predictive relationships for pesticide partitioning were developed.